Methods, algorithms, and tools for remote long-term monitoring of the safety of people and their property - Shevchuk, B.M. (KIBERNETYKA TA SYSTEMNYI ANALIZ, 2025)
The methodological and algorithmic foundations of the functioning of terminal, local-regional, and global wireless networks for long-term security monitoring of large groups of people and their property are proposed. Taking into account the operation of portable object systems of the monitoring network with many limitations, the operational processing and encoding of samples of monitoring signals and video data frames are proposed. The input monitoring data from sensors, transducers, and video modules is encoded based on the signal approach. According to this approach, the processing means of object systems in the process of filtering and compressing monitoring signals and images ensure accurate encoding, decoding, and restoration of the parameters of the most informative signal samples and video signal pixels, which include extrema and inflection points of the contour signals and video signals. It is proposed to protect the monitoring data arrays during the compression process with data protection using one-time ciphers. The article focuses on constructing energy-efficient and highly informative portable object systems for long-term monitoring of urban and rural residents, operators of human-machine systems and complexes, as well as mobile and stationary objects. Keywords: methods and algorithms for monitoring human safety, monitoring radio networks, object systems, processing, encoding and transmission of signals and images, compression and protection of monitoring data, one-time ciphers, crypto sequences.